A Survey of Information and Communication Technology Usage by Basic Technology Teachers in Selected Schools in Ilorin Metropolis - Onasanya , S. A.; Daramola, F. O.; Oputa , G. O. (International Journal of Educational Management, 2022)
In this paper, effort is made to determine the competency of teachers in the use of information and communication technology for teaching basic technology in questionnaire while selected secondary schools in Ilorin Metropolis. Sample of 60 respondents were randomly selected from the identified schools. The instrument used is a questionnaire while simple frequency counts and percentages were used to analyze and interpret the data. The analysis of the data revealed that information and communication technology facilities have not being often used, efficiently and effectively in most of the schools. The major recommendation is that Kwara State Government through the assistance of ministry of education should ensure proper training of basic technology teachers for effective utilization of information and communication technology facilities in the training of students in secondary schools